SHAPING A STORIES OF RESILIENCE MODEL FROM URBAN AMERICAN INDIAN ELDERS’ NARRATIVES OF HISTORICAL TRAUMA AND RESILIENCE - Reinschmidt, Kerstin M. (Am Indian Alsk Native Ment Health Res, 2016)
American Indians (AIs) have experienced traumatizing events but practice remarkable resilience to large-scale and long-term adversities. Qualitative, community-based participatory research served to collect urban AI elders’ life narratives on historical trauma and resilience strategies. A consensus group of 15 elders helped finalize open-ended questions that guided 13 elders in telling their stories. Elders shared multifaceted personal stories that revealed the interconnectedness between historical trauma and resilience, and between traditional perceptions connecting past and present, and individuals, families, and communities. Based on the elders’ narratives, and supported by the literature, an explanatory Stories of Resilience Model was developed.